Material-Oriented Life Reflected In Anne Stuart's Ruthless Novel (2010) A Marxist Approach - Wati, Yellis Erena Anggoro; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This study is about material oriented life in Ruthless novel. The problem of the study is how material oriented life is reflected in Ruthless novel. The object of the study is "Ruthless" novel by Anne Stuart. It uses marxism approach. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel and the secondary data is other materials related to the study. Technique of data collection is reading the content and other resources related to the novel, giving marks to particular parts, taking notes for important parts both in primary and secondary data resources, classifying the data into categories and drawing conclusion ad pedagogical suggestion. The technique ued in analyzig the data is descriptive analysis. The result of the study shows the following conclusion. Based on the analysis it can be concluded that the author delivers a moral message that some people believe that happines lies in the material achievement and the author reflects the social realities of American society at the late twentieth century and the early twenty first century which people give concerns to the issue of material oriented life.